2020
DOI: 10.1007/s00429-020-02125-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BDNF Val66Met on hippocampal subfields volumes and compensatory interaction with APOE-ε4 in middle-age cognitively unimpaired individuals from the ALFA study

Abstract: Background Current evidence supports the involvement of brain-derived neurotrophic factor (BDNF) Val66Met polymorphism, and the ε4 allele of APOE gene in hippocampal-dependent functions. Previous studies on the association of Val66Met with whole hippocampal volume included patients of a variety of disorders. However, it remains to be elucidated whether there is an impact of BDNF Val66Met polymorphism on the volumes of the hippocampal subfield volumes (HSv) in cognitively unimpaired (CU) individuals, and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Three studies specifically explored the association between hippocampal subfield volumetry and BDNF (brain-derived neurotrophic factor) Val66Met (rs6265) polymorphism. 36-38 Frodl et al (2014) showed significant interaction effects between BDNF Val66Met genotypes and childhood adversity within hippocampal subfields in a sample involving individuals diagnosed with MDD. On the one hand, the study highlighted that Met allele carriers with childhood adversity had smaller subfield volumes than Val allele homozygotes, where the most reduced volumes were specific for CA2/3 (β = −0.28, p = 0.015).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies specifically explored the association between hippocampal subfield volumetry and BDNF (brain-derived neurotrophic factor) Val66Met (rs6265) polymorphism. 36-38 Frodl et al (2014) showed significant interaction effects between BDNF Val66Met genotypes and childhood adversity within hippocampal subfields in a sample involving individuals diagnosed with MDD. On the one hand, the study highlighted that Met allele carriers with childhood adversity had smaller subfield volumes than Val allele homozygotes, where the most reduced volumes were specific for CA2/3 (β = −0.28, p = 0.015).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown an association of lower serum BDNF to widespread A␤ 42 in PET studies [6] and faster disease progression in Met carriers, and this effect is magnified by the presence of an Apolipoprotein E (APOE) 4 allele [7,8]. On the other hand, clinically healthy Val-Val individuals showed lower hippocampal volume compared to heterozygotes and with a dose-response effect with the number of APOE 4 alleles [9]. Older meta-analyses in both healthy and neuropsychiatric populations found no effects of Val66Met on brain volume.…”
Section: Introductionmentioning
confidence: 97%
“…It was also shown that Aβ oligomers exert a toxic influence on synaptic transmission by affecting synaptic long-term potentiation, as well as long-term depression, and might promote synapse loss in the hippocampus [ 15 ]. However, recent studies suggest that this effect might be compensated by the presence of one BDNF Met allele [ 16 , 17 ], but results on this remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…BDNF itself is a neuronal growth factor that plays an important role in the induction of neuronal sprouting and differentiation, and is highly expressed in the hippocampus [ 18 , 19 ]. Especially, the single-nucleotide polymorphism BDNF Val 66 Met, which causes a valine (Val) to methionine (Met) substitution at codon 66 of the BDNF protein, is of high interest because of its known influence on hippocampal functions [ 16 ]. It has also been associated with AD and depression in the past [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation